The Effect of Parental Support on Juvenile Delinquency in East Java - Fina Hidayati; Nurul Hartini; Achmad Chusairi (International Journal Labs, 2022)
Juvenile delinquency is a behavior carried out by adolescents by ignoring social values that apply in society. The behavior that appears in adolescents cannot be separated from how parental assistance is given to adolescents. Parental support is the support given by parents in several aspects, namely attention, finance, and information, in order to maximize the potential of adolescents so that they can develop optimally. This study aims to determine the effect of parental support on the tendency of delinquent behavior in adolescents in East Java. The method used is correlational with a sample involving 294 adolescents (aged 13-16 years) taken at random. Data collection uses the perceived parental support (PPS) scale (Alfgeir, 2010) and juvenile delinquency measurement (Syariful et al., 2020). The results show that parental support affects the tendency of delinquent behavior in adolescents with a p-value = 0.000 (<0.05), with the largest influence on informational support, 0.835, and the lowest on financial support, 0.423. The conclusion is that informational support and attention have a strong influence on the tendency of juvenile delinquency behavior, meaning that the higher the parental support, the lower the juvenile delinquency behavior.